2018
DOI: 10.1186/s12886-018-0763-9
|View full text |Cite
|
Sign up to set email alerts
|

The function and morphology of Meibomian glands in patients with thyroid eye disease: a preliminary study

Abstract: BackgroundTo investigate function and morphology of the meibomian gland (MG) in patients with thyroid eye disease (TED).MethodsIn this prospective case series study, patients with unilateral or bilateral TED were consecutively enrolled. The diagnosis of TED was based on the typical orbital findings and/or radiographic evidence. The disease activity of TED was classified according to the clinical activity score (CAS). Degrees of lagophthalmos and exophthalmos, blinking rates, and results of the Schirmer test 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 46 publications
(49 reference statements)
9
33
0
1
Order By: Relevance
“…We found that eyes with GO were characterized by greater MG dropout, tear lm instability (shorter BUT), and ocular surface epithelial damage (higher CFS), as well as worser MG secretion; some of these ndings were consistent with previous reports [27,43,44]. In our study, the SIT between the inactive GO group and controls showed no signi cant difference.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that eyes with GO were characterized by greater MG dropout, tear lm instability (shorter BUT), and ocular surface epithelial damage (higher CFS), as well as worser MG secretion; some of these ndings were consistent with previous reports [27,43,44]. In our study, the SIT between the inactive GO group and controls showed no signi cant difference.…”
Section: Discussionsupporting
confidence: 92%
“…However, in patients with active GO, tear secretion was signi cantly reduced, compared to the inactive GO group and controls. These results were consistent with some previous studies [13,44], although others demonstrated con icting ndings [27,51]. Eckstein et al [13] reported that high TSHR autoantibody activity in patients with active GO might impair the lacrimal gland, which could physiologically express TSHR.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…При контактной мейбографии (трансиллюминации) исследование проводят со стороны наружной поверхности века без его выворачивания (в этом случае МЖ имеют темный цвет) с использованием аппарата LipiView II Ocular Surface Interferometer, «TearScience, Inc.», а также аппарата для витрэктомии с оптиковолоконным источником света, снабженным устройством для трансиллюминации (Millenium system, «Bausch & Lomb», San Leandro, CA, СШA) [9,10,13]. Исследование структуры мейбомиевых желез при помощи конфокального микроскопа HRT (Heidelberg Retina Tomograph II -Rostock Cornea Module, «Heidelberg Engineering», Dossenheim, Германия) показало невысокое качество изображения [14,15]. Предпринимаются попытки визуализировать МЖ, используя аппараты OCT (Optical Coherent Tomograph) высокого разрешения когерентного инфракрасного света длиной волны 1060 нм, при этом полученные изображения также не были достаточно информативны [13,[16][17][18].…”
Section: Information About the Authorsunclassified